Steering vehicle control and road bank angle estimation: application for diagnosis of vehicle limits in bend. (9th March 2015) - Menhour, Lghani; Charara, Ali; Lechner, Daniel
This paper deals with the diagnosis of the critical driving situations. This work is divided into three parts: the first one presents two steering controllers using the sliding mode and the switched H∞ controllers, the second one describes an unknown input sliding mode observer, while the last one presents an approach to the diagnosis of critical driving situations. All existence conditions are established using the Lyapunov approach. Simulations are conducted to highlight the efficiency of the proposed approach using the experimental data recorded by an instrumented Peugeot 307 laboratory car. The diagnosis of the critical driving situations is achieved by the speed extrapolation concept using simultaneously a non–linear model, a steering control and road bank observer. The speed extrapolation concept is used in order to evaluate situations under high dynamic loads on a bend, using stability of the sideslip motion.